O processo de trabalho do enfermeiro na unidade de urgência e emergência de um hospital público - Barbara Ribeiro Martins (2016)
The aim of this study was to analyze work systems of nurses in Urgent Care Units at hospitals and Emergency Care Units at First-aid Centers, evaluating the connection between management and aiding tasks. A qualitative case study was chosen as the research method. The research took place at the Urgency and Emergency Units of a state-owned hospital. There were twenty participating subjects, all of whom are nurses occupying coordinating and aiding positions for longer than six months. Those enjoying vacations, as well as those on leave or who refused to participate, were not included. Data was collected, by means of semi-structured interviews, and subjected to content analysis. All phases of the research were carried out in compliance with Brazilian National Healthcare Council Regulation 466/2012 (Conselho Nacional de Saúde). Results were fit into three different categories: 1) Urgency and Emergency Units, whose research ambience was described as being a facilitator to work systems; 2) the nurses work systems at the Urgency and Emergency Units, which displayed both their main goal of saving lives and the work subjects who are the user and the team, aiming to offer quality and speedy assistance and cure or at least improve patients conditions; and 3) the possible connections between the coordinating and aiding work of nurses, which showed their tasks. Examples of aiding-nurses-related tasks are: providing care to patients under risky conditions, direct care of patients under critical conditions, infirmary supervision and care of patients under seemingly uncritical conditions. At the end of the study, its main conclusions were presented, out of which, the ones which stood out were the connected and complementing work systems between coordinating and aiding nurses, which bear great importance for patients within urgency and emergency contexts. The discussion over the work systems enabled to pinpoint characteristics, potentialities and existing challenges in urgency and emergency services, thus contributing to quality assistance in the realm of this research.